1991
DOI: 10.1902/jop.1991.62.1.2
|View full text |Cite
|
Sign up to set email alerts
|

The Excessive Loss of Branemark Fixtures in Type IV Bone: A 5‐Year Analysis

Abstract: The predictability of branemark implants has been well documented. High success rates in the maxilla and mandible in fully and partially edentulous patients can be expected. A host of factors may be attributed to the etiology of fixture loss. However, the quality of bone stands out as the single greatest determinant in fixture loss. Types I, II, and III bone offer good strength. Type IV bone has a thin cortex and poor medullary strength with low trabecular density. Ninety percent of 1,054 implants placed were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
511
3
24

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 842 publications
(549 citation statements)
references
References 2 publications
11
511
3
24
Order By: Relevance
“…The effect of a decrease in bone density on dentalimplant healing has been little investigated [2], and so far it is not known whether bone density and quality influence the favorable prognosis of dental implants. Jaffin and Berman [3] reported a higher failure rate for implants placed in bone with low bone mineral density (BMD) and an increase in the time of osseointegration, whereas Mori et al [4] observed inadequate bone formation adjacent to the implant. Von Wower et al [5] demonstrated that BMD is significantly lower in the oral cavity of patients with systemic osteoporosis than in normal subjects.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of a decrease in bone density on dentalimplant healing has been little investigated [2], and so far it is not known whether bone density and quality influence the favorable prognosis of dental implants. Jaffin and Berman [3] reported a higher failure rate for implants placed in bone with low bone mineral density (BMD) and an increase in the time of osseointegration, whereas Mori et al [4] observed inadequate bone formation adjacent to the implant. Von Wower et al [5] demonstrated that BMD is significantly lower in the oral cavity of patients with systemic osteoporosis than in normal subjects.…”
Section: Introductionmentioning
confidence: 99%
“…The implant failure rate in such sites has been reported to be greater than in bone qualities type I to III. 4,5,34,35 Therefore, more complications and failures are expected when inserting implants in patients with osteoporotic bone. 36 However, studies investigating whether osteoporosis is a risk factor for using implants in humans have revealed no correlation between possible implant failure and the severity of osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…A higher failure rate in patients with low bone quality, sometimes associated with small and inadequate bone volumes, has been reported. [4][5][6] Osteoporosis is characterized by a loss of bone mass with brittle bone tissue which increases susceptibility to fractures. This age-related disease is mainly seen among postmenopausal women 7 and may have a relationship with periodontal attachment and oral bone loss.…”
mentioning
confidence: 99%
“…No reports could be found on the clinical relevance of osteomalacia for the outcome of oral implants. It could be that some osteomalacia patients have been categorized as patients with "poor bone quality, " category IV bone, which has been clearly associated with a higher failure rate [ 29,30 ].…”
Section: Cmentioning
confidence: 99%